Effects of the Type of Accounting Standards and Motivation on Financial Reporting Decision - Kang, Gerui (Grace); Lin, Jerry W. (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2011)
This study explores whether the precision (type) of accounting standards influences management accounting reporting behaviors when an environmental variable, motivation, is incorporated. We predict that motivation affects managements financial reporting decision. When management has motivations to make aggressive reporting, they are more likely to do so than if they do not have such motivation. Furthermore, we posit that the type of accounting standard interacts with motivation and affects managements accounting decision. When management has motivation to report aggressively, with rules-based accounting standards, management is more likely to be guided by the precise numerical thresholds to achieve aggressive reporting than with principles-based accounting standards. We conduct a 2x2 between-subjects experiment. Ninety-six senior accounting students participate in this study. The results support our predictions that when management has motivation for aggressive reporting, they will make motivation-consistent accounting choice. Furthermore, under rules-based accounting standards, management is more likely to choose aggressive reporting than under principles-based accounting standards, when management has motivations to do so.